2020
DOI: 10.1007/s00442-020-04726-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tree crops and temperature on the timing of frugivorous bird migration

Abstract: Migration has evolved to tackle temporal changes in availability of resources. Climate change has been shown to affect the migration dates of species, which raises the question of whether the variation in the timing of migration is climate or resource dependent? The relative importance of temperature and availability of food as drivers of migration behaviour during both spring and autumn seasons has been poorly studied. Here, we investigated these patterns in frugivorous and granivorous birds (hereafter frugiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Changing weather conditions were also reported to influence the migration of palae-arctic migrants. Spring migration is mainly related to increasing temperatures, while autumn departure corresponds to decreasing air temperature in the breeding range 18 – 22 . Such behavioral responses correspond to changes in the corticosterone level to meet physiological needs in the early stage of migration, such as an increase in foraging frequency to enhance the body fat content (refueling) for the upcoming spring migration 3 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Changing weather conditions were also reported to influence the migration of palae-arctic migrants. Spring migration is mainly related to increasing temperatures, while autumn departure corresponds to decreasing air temperature in the breeding range 18 – 22 . Such behavioral responses correspond to changes in the corticosterone level to meet physiological needs in the early stage of migration, such as an increase in foraging frequency to enhance the body fat content (refueling) for the upcoming spring migration 3 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Snow cover may be a smaller disadvantage for species foraging in trees than for species feeding on the ground (Newton 2008), whereas cold spells will increase energy demands and may trigger southward migration and limit wintering in northern areas independent of foraging site (Ulfstrand 1963, Zuckerberg et al 2011. Kanerva et al (2020) found that temperature had little influence on the timing of autumn migration in Finland for a variety of irruptive species and facultative migrants. The study of Kanerva et al (2020) is also one of the few that have assessed the relative importance of crop size and weather, and found that crop size was most important for determining timing of autumn migration, including for all the rowanberry specialist species.…”
Section: Introductionmentioning
confidence: 94%
“…Kanerva et al (2020) found that temperature had little influence on the timing of autumn migration in Finland for a variety of irruptive species and facultative migrants. The study of Kanerva et al (2020) is also one of the few that have assessed the relative importance of crop size and weather, and found that crop size was most important for determining timing of autumn migration, including for all the rowanberry specialist species. Similarly, partial migration in many Finnish landbird species was influenced more by tree seed and berry crops than temperature (Meller et al 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, earlier spring migrants may experience worse weather conditions during migration, increasing their energy expenditure [ 10 ]. The consequences of variability in timing of the autumn migration are less well understood [ 11 , 12 ] and may be species specific [ 13 , 14 ], thus more challenging to determine. Nevertheless, autumn migration is marked by high mortality of juveniles on their first migration [ 15 ], as well as by the choice of wintering location [ 16 ] that may have carry over effects to the remaining annual cycle [ 17 ].…”
Section: Introductionmentioning
confidence: 99%